PEMBATASAN TERHADAP HAK ASASI MANUSIA DALAM PRESPEKTIF KEADAAN DARURAT - Osgar S Matompo (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Human rights is a gift from Allah SWT, as a consequence becoming human creature, therefore it couldn’t be deprived or abolished by the state. If a state in an abnormal condition or emergency condition, state is allowed to take an extraordinary action including giving restriction to human right for the sake of defending state integrity and protect its citizens, but human right that could be restricted is human right which is categorized in non-derogable right (right that couldn’t be limited in any kind of condition). This research found that in the practice of human right restriction which is applied in any kind of emergency condition in various area of Indonesia precisely touch the rights which are non-derogable rights.